STRESS AKADEMIK DAN FEAR OF FAILURE TERHADAP PROKRASTINASI AKADEMIK PADA SISWA MADRASAH ALIYAH - Munifah, Nabilah; Hanoum, Magdalena; Purwantini, Lucky (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik Universitas Islam 45 Bekasi, 2023)
The background of this research is based on the phenomenon of procrastination behavior which has been considered as a common thing and commonplace for students to do when doing assignments. This study aims to determine the relationship and influence of academic stress and fear of failure on academic procrastination in MAN 2 Cirebon students. This research uses correlational quantitative research methods. The subjects of this study were students of MAN 2 Cirebon class 10 – 11 as many as 138 students. The sampling technique used is the Non Probability Accidental Sampling technique. For the reliability test using resulting in a value of ralpha = 0.849 for the academic stress scale, ralpha = 0.881 for the fear of failure scale, and, r alpha = 0.931 for the academic procrastination scale. The results of the Spearman rank correlation test on academic stress on academic procrastination show that academic stress has a significant positive correlation with academic procrastination. While the fear of failure to academic procrastination is not significantly correlated. Then for the results of a simple regression test on academic stress on academic procrastination, it got a significance value of 0.003 (p <0.05), and a coefficient of determination value of 0.063, meaning 6.3%, meaning that student academic stress contributed 6.3% to the behavior of academic procrastination. students, while 93.7% was influenced by other factors not examined. So the conclusion from the simple regression results obtained that academic stress has a less significant effect on academic procrastination behavior in MAN 2 Cirebon students.